IMPLEMENTASI DALAM EDUKASI KUALITAS PELAYANAN OLEH CUSTOMER SERVICE DI BRI KANTOR CABANG BANDUNG MARTADINATA - Djenal Suhara; Lilis Putri Anggraeni (AL-INTIFA, 2023)
Providing services for every banking institution is an activity that is routinely carried out every day. This proves that the quality of service provided by each banking institution must be considered in order to achieve customer satisfaction. People who are directly involved in customer satisfaction are Customer Service Officers (CSOs). CSOs play a role in increasing customer satisfaction in order to maintain their loyalty. Banking institutions need professional human resources (HR) to enable the implementation of service excellence properly. Therefore, every CSO must be equipped with the ability and knowledge of qualified service excellence. In addition to the ability and qualified knowledge, another important thing in the implementation of service excellence which is related is communication. A CSO must understand very well how to properly interpersonal communication as it should be. Bank Rakyat Indonesia or BRI is one of the largest banks in Indonesia with a vision to become a leading commercial bank that always prioritizes customer satisfaction and pays great attention to service excellence. Research location at Bank Rakyat Indonesia, Bandung Martadinata Branch Office. The object of research in this study is the services provided by CSOs with the implementation of service excellence to the customers. From the research results it can be rejected that there are increases and decreases in the number of customers who use Customer Service services. This is the author's consideration to examine how the implementation of excellent service to customers at the bank with the dimensions of service quality.